INTERPRETASI TRANSMISIVITAS UNTUK ANALISA POTENSI AIR BAWAH TANAH BERDASARKAN DRAWDOWN AIR SUMUR CINCIN MENGGUNAKAN METODE PUMPING TEST DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Rigia Givanny Pritamara; Juandi M; Usman Malik (Universitas Riau, 2019)
The most consumption water is groundwater taken through excavated wells or ring wells. An aquifer test can be applied in pump test in order to find transmissivity of drawdown ring wells.The tested ring wells were located at 25 different locations in the Marpoyan Damai District. In the pumping test on the ring wells data was obtained namely drawdown test data s, times t, rate of discharge Q, and then create a graph of s/Q vs Q. The straight line that cut the s/Q axis the A value with the C gradient and the determinant coefficient d2. The values obtained were then inserted into the transmisivity formula of the Cooper-Jacob method. The A values for t = 3 minutes and t = 7 minutes were selected because their results in C values are close to each other. The C values of t = 3 minutes and t = 7 minutes are 0.1671 and 0.1672 respectively. Transmissivity value obtained is 134.5 m2/day. The value shows a potentially useful groundwater aquifer for the Marpoyan Damai district because the transmissivity value exceeded 50 m2 / day.